2010
DOI: 10.1103/physrevlett.105.038501
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Geometry of Ocean Flows

Abstract: We introduce a new global Lagrangian descriptor that is applied to flows with general time dependence (altimetric datasets). It succeeds in detecting simultaneously, with great accuracy, invariant manifolds, hyperbolic and non-hyperbolic flow regions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
146
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(146 citation statements)
references
References 13 publications
0
146
0
Order By: Relevance
“…Another distinguishing characteristic of the MET is that the convergence to its asymptotic value is always monotone in time whereas in all the other quantifiers convergence to their asymptotic values is oscillatory (except the arc-length map [34,35] which is monotone yet unbounded). Hence we expect that the convergence of the MET will be faster and more regular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another distinguishing characteristic of the MET is that the convergence to its asymptotic value is always monotone in time whereas in all the other quantifiers convergence to their asymptotic values is oscillatory (except the arc-length map [34,35] which is monotone yet unbounded). Hence we expect that the convergence of the MET will be faster and more regular.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the Lagrangian characteristics present the resulting observable after a certain integration time, with no information regarding the intermediate time dynamics (e.g. the AD and RD fields depend only on the initial and final location of the particles), whereas some of the other Lagrangian characteristics use averaging or integration along the trajectories [3,17,26,[33][34][35]. These Lagrangian fields are commonly used to identify regions of small and enhanced stretching and, in particular, are used to identify the spatial position of dividing surfaces between different regions, the Lagrangian Coherent Structures (LCS) [2,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Other techniques include DHTs (Ide et al, 2002;Ju et al, 2003) and the direct calculation of manifolds as material surfaces (Mancho et al, 2003(Mancho et al, , 2004(Mancho et al, , 2006b, the geodesic theory of Lagrangian coherent structures (LCS) (Haller and Beron-Vera, 2012) and the variational theory of LCS (Farazmand and Haller, 2012), etc. Our choice in this work will be the use of the Lagrangian descriptor (LD) function M introduced by Madrid and Mancho (2009) and Mendoza and Mancho (2010). The function M has been applied in a variety of geophysical contexts.…”
Section: Lagrangian Descriptorsmentioning
confidence: 99%
“…We have found that such POs can be obtained through a variational procedure based on Lagrangian descriptors (LDs). [36][37][38][39][40][41][42][43][44] The connection of the LD to the construction of POs is presented in Sec. II.…”
Section: Introductionmentioning
confidence: 99%